Chocolate Consumers and Lymphocyte-to-Monocyte Ratio: A Working Hypothesis from a Preliminary Report of a Pilot Study in Celiac Subjects - Raguzzini, Anna; Poce, Giovanna; Consalvi, Sara; Toti, Elisabetta; Palmacci, Francesca; Biava, Mariangela; Peluso, Ilaria (Antioxidants, 2019)
Background and aim: The aim of this work was to evaluate the relationship between platelet-to-lymphocyte ratio (PLR) and lymphocyte-to-monocyte ratio (LMR) with habitual consumption of dark chocolate in a group of celiac subjects in which chocolate consumption and lower neutrophil-to-lymphocyte ratio (NLR) association had already been observed. Additionally, due to the known anti-nutrient effect on iron absorption, we evaluated red blood cell count (RBC), mean corpuscular volume (MCV) and hemoglobin (Hb) values. Methods: Chocolate consumers and non-consumers were matched for sex, menopausal status, NLR values over the previously suggested cut off (2.32) for celiac patients, and co-morbidities. Results: Chocolate consumers had high LMR compared to non-consumers, whereas no differences were observed between chocolate consumers and non-consumers in RBC, MCV, Hb and PLR. However, similar number of subjects had PLR higher than the previously suggested cut off (143.7) for celiac disease. Conclusions: This preliminary report suggests a working hypothesis for larger studies aimed at establishing cut off values for LMR in celiac patients and the modulation of this marker by dietary antioxidants.